Philosophical Perspectives of Superior Values: An Attempted Redefinition as Identity and Heritage of Peoples - Galbán Rodríguez, Liuba; Rodríguez Matos, Neris (DIXI, 2017)
Purpose: To offer a redefinition of constitutional values by considering them as part of the identity and intangible heritage of peoples as a result of specific historical, political, economic and socio-cultural conditions. Description: A brief retrospective of the main conceptions of values in the legal philosophical thought iselaborated. Questions such as whether the recognition of values by constitutions arises from historical chance, why they are called “higher” or “superior” in the legal system, whether or not they are part of positive law, what their relationship to rights is, and whether their constitutional recognition is sufficient to enforce them in society are answered. Point of view: The values recognized in constitutions express ideologies, ideals and aspirations; they are reflections of social, political, legal philosophical thoughts and radiate to all the systems derived from theConstitution. Conclusions: Superior values are part of the identity and intangible heritage of peoples, especially when they are recognized because of democratic constituent processes, have the hierarchical supremacy of the source they come from, are part of positive law, and can be directly invokable, interpretable and applicable.
Keywords: axiology; constitution; rights; intangible heritage; constitutional supremacy; superior values